Simplified planar kinematic chain model of initial start phases in luging - Fedotova, V.; Pilipiv, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In the sport of luge the start plays an important role for an overall performance (Bruggemann et al., 1997). During the initial phases of the start, when an athlete is holding to the start handles, athlete`s body and the sled are forming a closed kinematic chain. The aim of the present study was to develop and evaluate limitations of a planar kinematic chain model for two initial start phases in luging. Methods: The closed kinematic chain was modelled using SimMechanics(TM) computer modelling environment. Kinematic drivers for the model were obtained from motion capture data (Yeadon and King, 2008); motion capture performed with 3 high-speed cameras at 100 fps using Simi Motion software. Segment inertia parameters estimated as in (de Leva, 1996; Zatsiorsky et al., 1990). Results: 4-, 5-, 6- (without leg segments) and 7-segment (with leg segments) models were developed. Testing of the models had shown that modelling the torso with one segment (4-segments model) is inappropriate for the selected movements. A model with two-segment torso gave a more realistic representation of the athlete`s performance. It was possible to simulate the movement adequately without hand and foot segments (5- and 7-segment models), however, adding the hand segment (6-segment model) improved the simulation. Discussion: During the initial start phases in the sport of luge movement of legs and arms is essentially three-dimensional; therefore modelling in-plane is an expected simplification. Nevertheless, the developed models can simulate the movement realistically in one plane. From the practical application perspective the planar models can be used as a first step in more sophisticated 3D modelling of the start phase in luging. As standalone models they can be used as a visualization tool in movement optimization procedure. The developed models are purely kinematically driven, as no force data was available to use as drivers. Deriving kinetic data from movement simulation is theoretically possible, but validation of the results is challenging as long as no reference measurements are available.